Adsorbent-based biogas quality analysis through purification process - Afisna, Lathifa Putri; Verdia, V Daniel; Syaukani, Muhammad; Saputra, Aprizal (Jurnal Pendidikan Teknologi Kejuruan, 2022)
Biogas is a raw material utilized to produced biogas. Biogas is renewable energy source produced by the anaerobic activity of organic matter through the fermentation process. Quality of biogas is determined by its main composition, such as methane (CH4). In addition, the composition of biogas also contains impurities such as unburnt carbon dioxide (CO2) so that it reduces the heating value, hydrogen sulfide (H2S) and water vapor (H2O) which are corrosive as well as Nitrogen (N2). Adsorption method on the impurity compositions can be used to improve biogas quality. This research used a column purifier containing four adsorbents in the form of calcium hydroxide Ca(OH)2, iron gram (Fe2(O3)), zeolite and activated carbon with three volume variations 600 cm3, 900 cm3 and 1200 cm3. The results of biogas testing using gas chromatography showed that the best quality obtained from the 1200 cm3 volume of adsorbent. Methane content was increased up to 17.985% and the impurity gases were decreased, such as carbon dioxide in as much as 18.15%, hydrogen sulfide and water vapor in as much as 0.182%. The heat produced by unpurified biogas was 1518.312 kJ/m3 and the highest heating value after purification was 2108.22 kJ/m3. The biogas combustion resulted in a dominant blue flame color.The most optimum effectiveness of the technology resulted in an increase of the methane content up to 64.275%. Based on this research, the utilization of column purifier with the adsorption method was able to improve the quality of biogas